2013
DOI: 10.1371/journal.pone.0068433
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Quantitative Trait Loci Underlying Cold Tolerance in Rice Seedlings via High-Throughput Sequencing of Pooled Extremes

Abstract: Low temperature is a major limiting factor in rice growth and development. Mapping of quantitative trait loci (QTLs) controlling cold tolerance is important for rice breeding. Recent studies have suggested that bulked segregant analysis (BSA) combined with next-generation sequencing (NGS) can be an efficient and cost-effective way for QTL mapping. In this study, we employed NGS-assisted BSA to map QTLs conferring cold tolerance at the seedling stage in rice. By deep sequencing of a pair of large DNA pools acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 36 publications
6
125
0
Order By: Relevance
“…Here, we detected a major QTL for cold tolerance on chromosome 1 that was also detected in a bi-parental population in a previous report (Yang et al 2013). The LD decay analysis indicated that an approximately 579 kb region at the associated locus was a candidate region for further study (Fig.…”
Section: Identification Of Candidate Gene Controlling Cold Tolerancesupporting
confidence: 77%
See 1 more Smart Citation
“…Here, we detected a major QTL for cold tolerance on chromosome 1 that was also detected in a bi-parental population in a previous report (Yang et al 2013). The LD decay analysis indicated that an approximately 579 kb region at the associated locus was a candidate region for further study (Fig.…”
Section: Identification Of Candidate Gene Controlling Cold Tolerancesupporting
confidence: 77%
“…Additionally, except for qCTSD12-1, all of the QTLs for SD have been reported previously. Specifically, qCTSR1-2 and qCTSR5-2 detected in our study were also identified in a bulked segregant analysis (BSA) using high-throughput sequencing of pooled extremes (Yang et al 2013). qCTSR5-1 and qCTSR10-1 were detected in a previous study by linkage mapping using bi-parents and their derived population under low-temperature stress (Jiang et al 2006).…”
Section: Gwas Analysis For Cold Tolerance At the Bud Burst Stagesupporting
confidence: 65%
“…The MYBS3 transcriptional network responds more slowly than the CBF pathway to low temperatures, regulating low-temperature tolerance genes such as those involved in the repression of the CBF pathway, which distinguishes it as an independent low-temperature responsive cascade 120 . In addition, several QTLs [121][122][123] have been identified that may be exploited to obtain low-temperature yield stability in rice.…”
Section: Solutions For Aluminium and Boron Toxicitymentioning
confidence: 99%
“…In our study, two QTLs qRC10 - 1 and qRC10 - 2 were identified on the same chromosome in DX. A QTL for cold tolerance ( qCTSS-10 ) was also identified in seedlings by Yang et al [52]. qCTSS-10 for 7°C cold treatment was mapped by high-throughput sequencing in the F 3 mapping population from a cross between a cold-tolerant japonica rice variety (Nipponbare) and a cold-sensitive indica variety.…”
Section: Discussionmentioning
confidence: 99%